Multi-element conjugated polymer as well as preparation method and application thereof

Through the design of multivariate random conjugated polymers and quaternary copolymerization method, the problem of polymer solar cell materials being difficult to take into account both solubility and molecular weight, achieving high molecular weight and efficient polymer synthesis and device performance improvement, supporting polymers The commercial development of solar cells.

CN119285910APending Publication Date: 2025-01-10SHANGHAI ZHUYANG NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310838732.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-10

Smart Images

  • Figure CN119285910A_ABST
    Figure CN119285910A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-element conjugated polymer and a preparation method and application thereof, the multi-element conjugated polymer has the following basic unit structure: # imgabs0 #, D1 and D2 are strongly crystallized electron-rich conjugated units, A1 and A2 are strongly crystallized electron-deficient conjugated units, and n = 50-1000. The preparation method comprises the following steps: carrying out copolymerization on D1, D2, A1 and A2 in the presence of a palladium catalyst, settling, carrying out suction filtration, extracting and drying to obtain the multi-element conjugated polymer. The multielement conjugated polymer prepared by the invention not only can maintain the original high crystallinity, but also can obtain higher molecular weight, and is beneficial to forming a better polymer-polymer interpenetrating network and optimizing the morphology of an active layer; in addition, due to random arrangement of the multi-element units of the main framework, the orbit degeneracy degree of the whole molecule is reduced, the spectrum of the polymer is blue-shifted, the device voltage can be effectively improved, and the application prospect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic materials, and relates to a multi-component conjugated polymer, a preparation method and application thereof, and in particular to a multi-component copolymer donor, a preparation method thereof and application of the copolymer donor in optoelectronic functional devices. Background Art

[0002] In recent years, as the energy crisis becomes increasingly prominent, solar energy, an inexhaustible green energy, has become the most ideal energy source. The collection and utilization of solar energy has become one of the hot topics in scientific research. In particular, polymer solar cells have gained popularity due to their many advantages, such as low cost, low energy consumption, and roll-to-roll large-area printing to produce flexible devices. With the unremitting efforts of many scientific researchers, with the advent of a large number of high-efficiency conjugated polymers, coupled with the careful design and optimization of the structure of polymer solar cell devices, the photoelectric conversion efficiency of polymer solar cells has now increased to more than 19%, which fully demonstrates the huge commercial value of polymer solar cells.

[0003] The excellent performance of polymer optoelectronic materials in organic solar cells mainly comes from the fact that high molecular weight polymers can form a dense network interpenetrating structure in the active layer, which is not only conducive to the transfer of charges, but also can stabilize the morphology, thereby improving the overall stability of the battery and increasing the service life. The crystallinity and molecular weight of the polymer will affect whether the polymer can form a continuous fiber phase in the device. High crystallinity is conducive to inducing crystallization between polymers; and high molecular weight can help polymers form entanglements, which is conducive to the formation of a continuous phase; however, highly crystalline monomers and excessively high polymerization degrees will cause the solubility of the polymer to drop sharply, making it difficult to dissolve, which is contrary to the solution-processed organic solar cell process. Therefore, the control of the molecular weight of high crystalline polymer donor materials has become a major difficulty in the further industrialization of high-performance polymer materials, which has also largely restricted the further development of polymer solar cells on the road to commercialization.

[0004] Therefore, it is of great practical significance to develop a polymer donor material that can achieve both good solubility and high molecular weight. Summary of the invention

[0005] Due to the above-mentioned defects in the prior art, the present invention provides a polymer donor material that can achieve both good solubility and high molecular weight, thereby overcoming the defect that the prior polymer donor material is difficult to achieve both good solubility and high molecular weight at the same time.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A multi-conjugated polymer having the following basic unit structure:

[0008]

[0009] Wherein, D1 and D2 are strongly crystalline electron-rich conjugated units, A1 and A2 are strongly crystalline electron-deficient conjugated units, and n=50-1000;

[0010] The D1 and D2 are selected from the following groups which are unsubstituted or have substituents:

[0011]

[0012] In the formula, R1 is selected from hydrogen, an alkyl group having 1 to 30 carbon atoms, an alkoxy group having 1 to 30 carbon atoms, a cyano group, a nitro group, an ester group, an aryl group, an aralkyl group, a halogen group, a halogenated alkyl group, a heteroalkyl group, an alkenyl group, and an aryl group substituted with a single bond, a double bond, a triple bond, or a combination thereof, and the Y atom is selected from one of oxygen, sulfur, and selenium;

[0013] The A1 and A2 are selected from the following groups which are unsubstituted or have substituents:

[0014]

[0015] In the formula, R2 is the same or different hydrogen, a straight chain or branched chain alkyl group having 8 to 20 carbon atoms, a cycloalkyl group having 8 to 20 carbon atoms, a straight chain or branched chain alkoxy group having 8 to 20 carbon atoms, a straight chain or branched chain alkoxy group having 8 to 20 carbon atoms, or an aryl group containing one or more aromatic rings, and X is a hydrogen atom, a fluorine atom, a chlorine atom, an alkyl group, an alkoxy group, an alkylthio group, an aralkyl group, an acyl group, an acyloxy group, an acylthio group, an ester group, an amine group, an amide group, an imide group, an alkenyl group, an alkynyl group, a carboxyl group, a cyano group, a sulfone group, a sulfoxide group, an aryl group or a heterocyclic group.

[0016] The present invention adopts the method of multi-component random tool to simultaneously introduce two high-crystalline donor units and two high-crystalline acceptor conjugated units. The random arrangement of each donor and acceptor unit reduces the aggregation degree between polymers to a certain extent, greatly improves the molecular weight and solubility of the conjugated polymer, and realizes the simple synthesis of high molecular weight polymer synthesis.

[0017] The present invention also provides a method for preparing the above-mentioned multi-conjugated polymer, comprising the following steps:

[0018] 1) The tin compound of D1, the tin compound of D2, the A1 monomer and the A2 monomer are put into a reaction bottle and reacted under the protection of an inert gas, wherein D1 and D2 are strongly crystalline electron-rich conjugated units, and A1 and A2 are strongly crystalline electron-deficient conjugated units;

[0019] 2) After the reaction is completed, the reaction liquid is precipitated, filtered, extracted, and dried to obtain a multi-component conjugated polymer.

[0020] The above method is simple and has good repeatability, which plays a positive role in reducing the production and processing costs of polymer solar cells and provides a reliable basis for the early commercialization of polymer solar cells.

[0021] As the preferred technical solution:

[0022] In the method described above, step 1) before the reaction, the catalyst and solvent are added after multiple replacement of the gas;

[0023] The reaction time of the reaction is 12 to 24 hours;

[0024] The ratio of the sum of the amounts of D1 and D2 to the sum of the amounts of A1 and A2 is 1:1.

[0025] The method as described above, wherein the catalyst is at least one of tetrakistriphenylphosphine palladium and bis(dibenzylideneacetone palladium);

[0026] The solvent is one of toluene, xylene, chlorobenzene, dichlorobenzene or a mixed solution thereof.

[0027] In the method as described above, step 2) is specifically to precipitate the reaction solution in ethanol, and then, after suction filtration, extract with acetone, n-hexane, and dichloromethane respectively, and finally extract with chloroform to obtain a chloroform solution of the polymer, and after rotary evaporation and concentration of the chloroform solution of the polymer, precipitate in ethanol again, suction filter, and finally dry to obtain a multi-conjugated polymer.

[0028] In addition, the present invention also provides an application of the multi-conjugated polymer as described above in an organic solar device, wherein the multi-conjugated polymer is blended with a polymer receptor and used as an active layer of the organic solar device.

[0029] The above technical solution is only a feasible technical solution of the present invention, and the protection scope of the present invention is not limited thereto. Those skilled in the art can reasonably adjust the specific design according to actual needs.

[0030] Invention mechanism:

[0031] The present invention can reduce and improve the solubility of the intermediates in the polymerization process of the polymer to a certain extent through the method of quaternary random copolymerization, avoid precipitation due to reduced solubility and stop the reaction; the polymer monomers can be further effectively polymerized, thereby achieving the purpose of high molecular weight, high crystallinity, and solution-processable high-performance polymers.

[0032] The present invention utilizes monomers of a variety of high-performance polymers, and through a quaternary copolymerization method, regulates the crystallinity and molecular weight of the polymer to synthesize a polymer with high molecular weight and high photovoltaic performance. This method can improve the problem of reduced solubility of the polymer during the polymerization process, thereby stopping the polymerization, to a certain extent; by further increasing the degree of polymerization of the polymer, longer polymer fibers can be obtained. Experiments have shown that by synthesizing polymers through quaternary random copolymerization, the molecular weight of the polymer material can be increased from the original 35kDa to 55KDa, the morphology of the active layer has also been optimized, and the device performance has been significantly improved.

[0033] The method of the present invention is simple and easy to operate. It mainly synthesizes a high molecular weight conjugated polymer by a random copolymerization method of a high-performance donor-acceptor unit. The molecular weight of the random polymer can be effectively regulated by the ratio between the quaternary components, so that it can be more effectively polymerized without precipitation in the solution, thereby obtaining a high molecular weight polymer material. When blending with an acceptor material to prepare an active layer of an organic solar cell, a better phase morphology is obtained, and the mobility and filling factor can also be effectively improved. In addition, the higher mobility is also conducive to the preparation of thick film devices, which has a very important reference value for large-area printed solar cells produced by a roll-to-roll process.

[0034] The above invention has the following advantages or beneficial effects:

[0035] (1) The multi-component conjugated polymer of the present invention introduces quaternary random copolymerization into the design of polymer donor materials, greatly improving the molecular weight and solubility of the conjugated polymer;

[0036] (2) The preparation method of the multi-conjugated polymer of the present invention has a simple process and mild reaction conditions, and is highly feasible. It can effectively increase the molecular weight of the polymer and ensure its solubility. This has important reference value for the large-scale preparation of polymer solar cells in the future and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The present invention and its features, appearance and advantages will become more apparent by reading the detailed description of non-limiting embodiments with reference to the following drawings. The same reference numerals indicate the same parts in all the drawings. The drawings are not drawn to scale, and emphasis is placed on illustrating the subject matter of the present invention.

[0038] Figure 1 The schematic diagram of the device structure of the inverted organic solar cell prepared in Application Example 1;

[0039] Figure 2 This is a current density-voltage test curve of the inverted organic solar cell prepared in Application Example 1. DETAILED DESCRIPTION

[0040] The structure of the present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but is not intended to limit the present invention.

[0041] Example 1

[0042] A method for preparing a multi-conjugated polymer, the steps are as follows:

[0043] 0.5 g (4,8-bis (5- (2-ethylhexyl) -4-fluorothienyl) benzo [1,2-B: 4,5-B'] dithienyl) bistrimethyltin and 0.4 g 1,3-bis (5-bromothiophene) -5,7-bis (2-isooctyl) benzo [1,2-c: 4,5-c'] dithiophene-4,8-dione and 50 mg 1,3-bis (5-bromo-4- (2-isooctyl) thiophene) -5,7-bis (2-isooctyl) benzo [1,2-c: 4,5-c'] dithiophene-4,8-dione were added to the reactor, 30 ml toluene solvent and 3 ml DMF were added, and the mixture was heated to 110 ° C. After deoxygenation three times, 18 mg tetrakis triphenylphosphine palladium was added to start the reaction, and the reaction was allowed to react for 24 hours. After stopping the heating and cooling to room temperature, the reaction solution was precipitated in ethanol. The obtained polymerization product was precipitated again in ethanol / water (10:1) and filtered. The collected product was extracted with acetone, n-hexane, toluene, dichloromethane and chloroform in a Soxhlet extractor in sequence. The chloroform extract was concentrated and precipitated again in methanol / water (10:1), filtered and dried to obtain a high molecular weight polymer donor material with a yield of 96% and a molecular weight of 52,000.

[0044] Example 2

[0045] A method for preparing a multi-conjugated polymer, the steps are as follows:

[0046] 0.5g (4,8-bis (5- (2-ethylhexyl) -4-fluorothienyl) benzo [1,2-B: 4,5-B'] dithienyl) bistrimethyltin and 0.4g 1,3-bis (5-bromothiophene) -5,7-bis (2-isooctyl) benzo [1,2-c: 4,5-c'] dithiophene-4,8-dione and 40mg 1,3-bis (5-bromo-3,4- (2-isooctyl) thiophene) -5,7-bis (2-isooctyl) benzo [1,2-c: 4,5-c'] dithiophene-4,8-dione were added to the reactor, 30ml toluene solvent was added, and the mixture was heated to 110°C. After deoxygenation three times, 9mg bis dibenzylidene acetone palladium was added to start the reaction, and the reaction was carried out for 24h. After stopping the heating and cooling to room temperature, the reaction solution was precipitated in ethanol. The obtained polymerization product was precipitated again in ethanol / water (10:1) and filtered. The collected product was extracted with acetone, n-hexane, toluene, dichloromethane and chloroform in a Soxhlet extractor in sequence. The chloroform extract was concentrated and precipitated again in methanol / water (10:1), filtered and dried to obtain a high molecular weight polymer donor material with a yield of 94% and a molecular weight of 58,000.

[0047] Comparative Example 1

[0048] A method for preparing a binary copolymer, the steps are as follows:

[0049] Dissolve 0.945g (4,8-bis (5- (2-ethylhexyl) -4-fluorothienyl) benzo [1,2-B: 4,5-B'] dithienyl) bistrimethyltin and 0.766g 1,3-bis (5-bromothiophene) -5,7-bis (2-isooctyl) benzo [1,2-c: 4,5-c'] dithiophene-4,8-dione in 10mL toluene, heat to 110°C, deoxygenate three times, then add 5mg tetrakis triphenylphosphine palladium to start the reaction, and react for 24h. Stop heating and cool to room temperature, then precipitate the reaction solution in ethanol. The obtained polymerization product was precipitated again in ethanol / water (10:1) and filtered. The collected product was extracted with acetone, n-hexane, toluene, dichloromethane and chloroform in a Soxhlet extractor in sequence. The chloroform extract was concentrated and precipitated again in methanol / water (10:1), filtered and dried to obtain a high molecular weight polymer donor material with a yield of 91% and a molecular weight of 32,000.

[0050] Application Example 1

[0051] The polymer described in Example 1 is blended with L8-BO and used as the active layer of an organic solar cell device to realize a high-efficiency organic thin-film photovoltaic device. The device is prepared by spin coating. The device structure of the organic solar cell is as follows: Figure 1As shown, from bottom to top, they are glass substrate / indium tin oxide (ITO) / electron transport layer / active layer / hole transport layer / silver (Ag). The specific preparation steps are as follows:

[0052] Step 1: The patterned ITO glass was ultrasonically cleaned with glass cleaning solution, deionized water, acetone, and isopropanol for 20 minutes in sequence, and the surface was blown dry with an air gun.

[0053] Step 2: The dried ITO glass is surface treated with a UV-ozone machine or a plasma cleaning machine. The UV-ozone machine treatment time is about 15 minutes, and the plasma cleaning machine treatment time is about 1 minute. Then, the ethanol solution of zinc oxide nanoparticles is spin-coated on the ITO glass sheet treated in step 1 at a speed of 3000 rpm, and then heated at 100°C for 10 minutes.

[0054] Step 3: The polymer described in Example 1 and the small molecule electron acceptor L8-BO are blended in a mass ratio of 1:1.2, dissolved in chloroform solvent at a total concentration of 15 mg / mL to obtain an active layer solution, and then the additive diiodomethane (DIM) is added at a volume ratio of 0.25%, and stirred at room temperature for 1 hour to dissolve for use.

[0055] Step 4: Spin the active layer solution onto the substrate surface in step 3 at a spin coating speed of 2500 rpm to prepare an active layer, and then anneal on a hot plate at 90° C. for 5 minutes.

[0056] Step 5: Place the device in step 4 on a patterned mask and transfer it to a vacuum thermal evaporation coating apparatus, and evaporate 5 nm of molybdenum oxide and 150 nm of silver electrode at a vacuum degree of 1×10-6 mbar.

[0057] The current density-voltage of the prepared organic solar cell is as follows Figure 2 As shown, Voltage represents voltage, currentdensity represents current density. The device parameters are as follows: open circuit voltage Voc = 0.878 V, current density Jsc = 25.7 mA / cm2, fill factor FF = 79.2%, efficiency PCE = 17.9%.

[0058] Comparative application example 1

[0059] In this comparative application example, the binary copolymer described in comparative example 1 is blended with L8-BO as the active layer of an organic solar cell device, which can realize a high-efficiency organic thin-film photovoltaic device. The device is prepared by spin coating. The device structure of the organic solar cell is glass substrate / indium tin oxide (ITO) / hole transport layer / active layer / electron transport layer (PDINN) / silver (Ag) from bottom to top. The specific preparation steps are as follows:

[0060] Step 1: The patterned ITO glass was ultrasonically cleaned with glass cleaning solution, deionized water, acetone, and isopropanol for 20 minutes in sequence, and the surface was blown dry with an air gun.

[0061] Step 2: The dried ITO glass is surface treated with a UV-ozone machine or a plasma cleaning machine. The UV-ozone machine treatment time is about 15 minutes, and the plasma cleaning machine treatment time is about 1 minute. Then, the PEDOT:PSS is filtered and spin-coated on the ITO glass sheet treated in step 1 at a speed of 4000 rpm, and then heated at 150°C for 15 minutes.

[0062] Step 3: The binary copolymer described in Comparative Example 1 and the small molecule electron acceptor L8-BO are blended in a mass ratio of 1:1.2, dissolved in chloroform solvent at a total concentration of 15 mg / mL to obtain an active layer solution, and then the additive diiodomethane (DIM) is added at a volume ratio of 0.25%, and stirred at room temperature for 1 hour to dissolve for use.

[0063] Step 4: Spin the active layer solution onto the substrate surface in step 3 at a spin coating speed of 2500 rpm to prepare the active layer. Then anneal on a 90°C hot plate for 5 minutes. After cooling, spin coat the electron transport layer (PDINN, 0.5 mg / mL methanol solution) onto the active layer surface at a spin coating speed of 2500 rpm.

[0064] Step 5: Place the device in step 4 on a patterned mask and transfer it to a vacuum thermal evaporation coating apparatus, and evaporate a 150nm silver electrode at a vacuum degree of 1×10-6mbar.

[0065] The device parameters of the prepared organic solar cell are as follows: open circuit voltage V oc =0.871V, current density J sc =25.3mA / cm 2 , fill factor FF = 78.7%, efficiency PCE = 17.3%.

[0066] By comparing Example 1 with Comparative Example 1, Application Example 1 and Comparative Application Example 1, it was found that the quaternary random copolymerization further effectively polymerized the polymer monomers to obtain high-performance polymers with higher molecular weight. After applying them to organic thin-film photovoltaic devices, Test 1 found that the organic thin-film photovoltaic devices prepared by the method of the present invention also had significant improvements over the prior art.

[0067] Those skilled in the art should understand that those skilled in the art can implement variations by combining the prior art and the above embodiments, which will not be described in detail here. Such variations do not affect the essential content of the present invention, and will not be described in detail here.

[0068] The above describes the preferred embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned specific embodiments, and the devices and structures that are not described in detail should be understood to be implemented in a common manner in the art; any technician familiar with the art can use the above-disclosed methods and technical contents to make many possible changes and modifications to the technical solutions of the present invention without departing from the scope of the technical solutions of the present invention, or modify them into equivalent embodiments of equivalent changes, which does not affect the essential content of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention are still within the scope of protection of the technical solutions of the present invention.

Claims

1. A multi-conjugated polymer, characterized in that: It has the following basic unit structure: Wherein, D1 and D2 are strongly crystalline electron-rich conjugated units, A1 and A2 are strongly crystalline electron-deficient conjugated units, and n=50-1000; The D1 and D2 are selected from the following groups which are unsubstituted or have substituents: In the formula, R1 is selected from hydrogen, an alkyl group having 1 to 30 carbon atoms, an alkoxy group having 1 to 30 carbon atoms, a cyano group, a nitro group, an ester group, an aryl group, an aralkyl group, a halogen group, a halogenated alkyl group, a heteroalkyl group, an alkenyl group, and an aryl group substituted with a single bond, a double bond, a triple bond, or a combination thereof, and the Y atom is selected from one of oxygen, sulfur, and selenium; The A1 and A2 are selected from the following groups which are unsubstituted or have substituents: In the formula, R2 is the same or different hydrogen, a straight chain or branched chain alkyl group having 8 to 20 carbon atoms, a cycloalkyl group having 8 to 20 carbon atoms, a straight chain or branched chain alkoxy group having 8 to 20 carbon atoms, a straight chain or branched chain alkoxy group having 8 to 20 carbon atoms, or an aryl group containing one or more aromatic rings, and X is a hydrogen atom, a fluorine atom, a chlorine atom, an alkyl group, an alkoxy group, an alkylthio group, an aralkyl group, an acyl group, an acyloxy group, an acylthio group, an ester group, an amine group, an amide group, an imide group, an alkenyl group, an alkynyl group, a carboxyl group, a cyano group, a sulfone group, a sulfoxide group, an aryl group or a heterocyclic group.

2. A method for preparing a multi-conjugated polymer as claimed in claim 1, characterized in that: The following steps are involved: 1) The tin compound of D1, the tin compound of D2, the A1 monomer and the A2 monomer are put into a reaction bottle and reacted under the protection of an inert gas, wherein D1 and D2 are strongly crystalline electron-rich conjugated units, and A1 and A2 are strongly crystalline electron-deficient conjugated units; 2) After the reaction is completed, the reaction liquid is precipitated, filtered, extracted, and dried to obtain a multi-component conjugated polymer.

3. The method according to claim 2, characterized in that Step 1) before the reaction, the gas is replaced several times and then the catalyst and solvent are added; The reaction time of the reaction is 12 to 24 hours; The ratio of the sum of the amounts of D1 and D2 to the sum of the amounts of A1 and A2 is 1:

1.

4. The method according to claim 3, characterized in that The catalyst is at least one of tetrakistriphenylphosphine palladium and bis(dibenzylideneacetone palladium); The solvent is one of toluene, xylene, chlorobenzene, dichlorobenzene or a mixed solution thereof.

5. The method according to claim 3, characterized in that: Step 2) is specifically to precipitate the reaction solution in ethanol, and then, after suction filtration, extract with acetone, n-hexane, and dichloromethane respectively, and finally extract with chloroform to obtain a chloroform solution of the polymer, and then, after rotary evaporation and concentration of the chloroform solution of the polymer, precipitate in ethanol again, suction filter, and finally dry to obtain a multi-conjugated polymer.

6. The use of a multi-conjugated polymer in an organic solar device according to claim 1, characterized in that: The multi-conjugated polymer is mixed with a polymer receptor and used as an active layer of an organic solar device.